STUDENTS’ PERCEPTIONS OF USING BLOOKET AS A GAMIFIED LEARNING TOOL TO ENHANCE VOCABULARY AND READING COMPREHENSION IN SENIOR HIGH SCHOOL - Aldayana, Yunisma; Andriyanti, Erna (Journal of English Educational Study (JEES), 2025)
Education and technology have gone hand in hand in various aspects, including in the process of learning English. Blooket is one of gamified learning tool that usually used by teachers as one of the learning media which uses technology. It provides alternative ways to learn vocabulary and reading comprehension.  This research aims to provides the students’ perceptions related to the effectiveness of Blooket, since it remains an urge to be provided to support the teaching and learning process.  A qualitative approach is used by interviewing six second-years senior high school students in one of public school in Yogyakarta. The data is analysed use thematic analysis to provide clear and comprehensive result. The research finds that Blooket allows students to have better engagement and increase their motivation especially in learning vocabulary. Moreover, students feel that through Blooket as game-based learning, the learning process becomes more interactive. On the other hand, Blooket is found not really support students’ reading comprehension. This finding is a note for teachers and future researcher whether there are some factors that make Blooket does not work in certain class or not. This current research is expected to fill the knowledge gap related to the senior high school students’ perception in using Blooket as gamified learning tool in learning vocabulary and reading.